Comparative study between different digital and offset litho printing systems - Simonian, George Nubur (DESIDOC Journal of Library & Information Technology, 2003)
This paper is a comparative study of the output quality and performance parameters of then most widely used digital colour printing presses and systems, acceptability tests for comparing the performance of the systems. http://dx.doi.org/10.14429/dbit.23.1.3590